Organic farming for sustainable agriculture/ (Acc. :D2277) (India : Agrobios, 2002)
Book Summary of Organic Farming For Sustainable Agriculture Table of Contents 1. Organic Farming: An Overview, 2. Sustainable Agricultural Systems: The World Scenario, 3. Management of Agricultural Pollution: Soil Pollution, 4. Management of Agricultural Pollution: Agrochemicals, 5. Use of Traditional Additives for Organic Farming, 6. Use of Non-Traditional Additives for Organic Farming, 7. Agricultural Waste Management and Crop Production, 7. Biogas Technology for Organic Farming, 9. Waste Water Treatment and use for Organic Farming, 10. Domestic and Industrial Wastes for Organic Farming, 11. Future Trends in Organic Farming, 12. References.
Include bibliographical references.
Keywords: 1. Organic farming 2. Sustainable agriculteure